Formulation, Dosage, and Exposure Time of Natural Substances in Controlling Aedes aegypti Larvae - Ahyanti, Mei; Yushananta, Prayudhy (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The incidence of vector-borne diseases in Indonesia, particularly Dengue Hemorrhagic Fever (DHF), continues to escalate. This surge correlates with climate change, the extreme transition from hot to rainy seasons. The use of synthetic chemicals for control measures can also poses environmental risks; hence, there is a necessity to explore natural control methods by harnessing the biodiversity of plant species within the environment. This research aims to assess the effectiveness of botanical extract mixture on the mortality of Aedes aegypti larvae.  Method: This study utilizes an experimental design with a complete factorial random arrangement, which aimed at elucidating the effectiveness of plant extract as a bio-larvacide against Aedes aegypti mosquitoes. The effectiveness is measured through larval mortality rates based on a formulated equation, with dosage and exposure time as the research variables. The research was conducted in the Environmental Health Departement Laboratory at Health Polytechnic of Tanjungkarang from March to July 2023. The observational sheet serves as the instrument The collected data are processed and analysed using ANOVA to discern variations in larva mortality based on the formula, linear regression is applied to explore the influence of dosage and exposure time on larva mortality. Result: The result of this study exhibits that the most efficacious formulations to terminate larvaes  were determined to be the 9th, 10th, and 11th formulations.  Furthermore, an extended exposure time correlates with the escalating rate of larval demise. The statistical model prosperously accounts for 88,59% of the variability in the response pertaining to Aedes larval mortality.  Conclusion: This study discerns that individually, the formula, dosage, and exposure time, also demonstrates an impact on larval death. This study unveils that an insecticidal formula derived from soursop leaves yields a higher mortality effect compared to formulations based on other materials.